Perspectiva y prácticas de educación-investigación participativa - Garrido García, Fco. Javier (Política y Sociedad, 2007)
Education and research in social sciences are in a deep process of change that shows inadequacy of traditional practices of elaboration, transmission and application of knowledge to face the formative necessities in current society. Specialized, individualist and competitive academic formation; disconnection between that academic formation and later professional practice; separation between theory and practice, among research and education in the educational processes; the annulment of dialogue between different interests and social knowledge; they are some problems it demand innovative solutions it should come from new research and education perspective. It is the challenge that we concern in this article, in which intends an participant education and action/research perspective to respond to the current problems in constructing knowledge and making formation to experts in social topics. Exposition is sustained in two axes: epistemológic-scientific and strategic-practical; on one hand the basic postulates of a process of participant education-research are exposed, and on other, we advance in elaboration of operative proposals to transforming the investigating and educating work. Everything is illustrated with examples of the pedagogic experience developed during more than 10 years in different courses.